(untitled) (Journal of Bio-Science, 2014)
Context: The application of encapsulated shoot tips and nodal segments may contribute to the protection of rare and threatened medicinal plants. Although the artificial seed technique has been reported for more than two decades, for medicinal plants this method has not been developed sufficiently. The main limitations in conventional propagation of some species with medicinal value are: reduced endosperm, low germination rate and seedless varieties. The above mentioned reasons indicate the need for the production of artificial seeds as a technique which combines the advantages of clonal multiplication with those of seed propagation and storage. Objectives: The objective of the present investigation was to standardize artificial seed production technology taking shoot tip and nodal explants in Mentha arvensis and its in vitro regeneration Materials and Methods: Sodium alginate beads were produced by encapsulation of shoot tip and nodal segments of the plant M. arvensis. MS medium was used as basal medium with agar and sodium alginate was used as gelling agent accompanied by CaCl2 solution. Results: Different concentrations and combinations of BAP, Kin and NAA were used in alginate bead in MS basal medium. Among the different concentrations of phytohormone, highest 80% of shoot formation was observed in MS medium containing 2.0 mg/l BAP + 0.2 mg/l NAA from nodal segments of M. arvensis. Highest average number of shoot 9.87 ± 0.58 formation was obtained in the same medium but highest length of shoot 6.27 ± 0.29 cm was found in the medium having 1.0 mg/l BAP + 0.5 mg/l NAA. Conclusion: The present investigation clearly established and demonstrated the method of obtaining the artificial seed production in M. arvensis supported by different hormone concentrations DOI: http://dx.doi.org/10.3329/jbs.v20i0.17722 J. bio-sci. 20: 99-108, 2012